Lessons from the American experiment with market-based environmental policies - Robert N. Stavins (Fondazione Eni Enrico Mattei (FEEM), 2002)
This paper provides an overview of the U.S. experience with market-based instruments with four categories: emission charges, tradeable permit systems,market friction reduction, and government subsidy reduction. Following that, I examine normative lessons that can be learned from these experiences, and then focus on positive political economy lessons. A final section offers some conclusions
Keywords: 330; environmental policy; market-based instruments; economic-incentive instruments; Umweltpolitik; Ökosteuer; Emissionshandel; Marktmechanismus; USA